Food-Borne Vibrio parahaemolyticus in China: Prevalence, Antibiotic Susceptibility, and Genetic Characterization - Li, Yanping; Xie, Tengfei; Pang, Rui; Wu, Qingping; Zhang, Jumei; Lei, Tao; Xue, Liang; Wu, Haoming; Wang, Juan; Ding, Yu; Chen, Moutong; Wu, Shi; et al. (Frontiers in Microbiology, 2020)
Vibrio parahaemolyticus is a marine and estuarine bacterium that causes damage of aquatic industry by foodborne outbreaks and possesses an enormous threat to food safety as well as human health worldwide. In the current study, we investigated 905 food samples (Ready-to-Eat foods, fish and shrimp) from 15 provinces in China, and aimed to determine the biological and genetic characteristics of potential V. parahaemolyticus isolates. Firstly, 14.17 % of 240 fish samples, 15.34 % of 365 shrimp samples and 3.67 % of 300 RTE food samples were positive for potential V. parahaemolyticus. Secondly, the rate of V. parahaemolyticus detection in summer reached 14.87 %, while it only reached 7.26 % in winter. Thirdly, we detected 202 V. parahaemolyticus strains for further research. And the antimicrobial resistance patterns of these foodborne isolates to 12 antimicrobial agents revealed that most of the isolates were resistant to ampicillin (79.20 %). At the same time, 73.27 % of the isolates were multi-drug resistant. The results showed that the isolates positive for the tdh and trh genes were up to 9.90 % and 19.80 % of all isolates. Besides, multiplex PCR test showed that the isolates of the O2 serogroup were the most prevalent. Furthermore, sequence types (STs) were obtained via multi-locus sequence typing, including 82 STs, 41 of which were newly identified. Thus, our findings demonstrated the high contamination rates of V. parahaemolyticus in fish and shrimp and it may pose a huge risk for consumers, especially in areas where seafood are eaten. We also provided up-to-date dissemination of antibiotic-resistant V. parahaemolyticus which is important to ensure the high efficacy in the treatment of human and aquatic products infections. Lastly, 46 of 108 V. parahaemolyticus strains possessed novel STs, which significantly revealed the high genetic diversity of the isolates tested. All of our research improved our understanding on microbiological risk assessment in Ready-to-Eat foods, fish and shrimp.